2004
DOI: 10.1136/vr.154.12.365
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological findings in sheep from Sardinia showing neurological signs of disease

Abstract: Histopathological and bacteriological examinations were performed on 178 brains from Sardinian sheep which were showing neurological signs. The sheep represented the total number of sheep with neurological syndromes submitted for diagnostic investigations over a three-year period in Sardinia. Scrapie was detected in 57 cases, cerebrocortical necrosis in 25, intoxication by a typical Mediterranean plant (Cistus species) was suspected in 25, coenurosis was detected in 11 cases, Listeria monocytogenes in eight ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
2
16
0
2
Order By: Relevance
“…These results agreed with Achenef et al (1999) who also observed large number of C. cerebralis cysts in brain of sheep. The clinical signs of variable degree, observed in the present study were more or less similar to those reported by Ligios et al (2004) . There was extensive damage to brain tissue leading to necrosis.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results agreed with Achenef et al (1999) who also observed large number of C. cerebralis cysts in brain of sheep. The clinical signs of variable degree, observed in the present study were more or less similar to those reported by Ligios et al (2004) . There was extensive damage to brain tissue leading to necrosis.…”
Section: Resultssupporting
confidence: 91%
“…Information on various aspects of this condition in sheep from many countries of the world in recent past has been furnished by number of workers viz. Doherty et al (1989) from Ireland, Achenef et al (1999) from Ethiopia, Abo-Shehada et al (2002) from Jordon, Ligios et al (2004) from Sardinia and Ozmen et al (2005) from Turkey. Though sheep is the main source of livelihood for Ashiyaran (nomadic people) in Iran and mutton constitute a major part of human diet in this country, still except for ~ "For correspondence: Tel: 0098-711-8231093; E-mail: nasrinmoghadar@yahoo.com sporadic reports on the occurrence of this infection in this animal from certain parts (Eslami, 1997), no information on different aspects of this infection in sheep is yet available from Fars Province of this country and hence the present study was undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Os achados de necropsia e histopatológicos foram semelhantes ao descritos em casos de PEM em pequenos ruminantes (Ligios et al 2004, Lima et al 2005, Guedes et al 2007. A PEM é uma enfermidade de etiologia multifatorial (Gould 1998) e, semelhante ao que ocorreu nos casos deste estudo, a maioria dos casos da doença descritos no Brasil permanece sem causa estabelecida (Schild et al 2005).…”
Section: Doença Sinais Clínicos Achados De Necropsia Histopatologiaunclassified
“…O diagnóstico foi realizado com base nos achados histopatológicos e confirmado por imunohistoquímica em seções de tronco encefálico dos dois ovinos afetados. As doenças neurológicas de ovinos diagnosticadas nesses 18 anos abrangidos por este estudo não diferenciaram substancialmente das doenças diagnosticadas em estudos similares realizados em outras regiões do Brasil (Guedes et al 2007) e do mundo (Ligios et al 2004). As caracterís-ticas dessas doenças, no entanto, podem apresentar variações dependendo da região de ocorrência (como ocorre com a listeriose e a raiva).…”
Section: Doença Sinais Clínicos Achados De Necropsia Histopatologiaunclassified
“…There is no doubt that the ewe had histopathological and immunohistochemical features in the obex region that were characteristic of encephalitic listeriosis. A sheep affected with atypical scrapie may display circling and additional symptoms, but other neurological diseases that cause similar clinical signs, particularly listeriosis, should be considered along with atypical scrapie [15, 17]. In the present case, abnormal behavior observed prior to culling might have been a result of the meningoencephalitis that was caused by Lm.…”
mentioning
confidence: 90%